KUALITAS DAGING DAN BAGIAN TUBUH LAIN TRENGGILING (MANIS JAVANICA DESMAREST, 1822) - Farida, Wartika Rosa (JURNAL BIOLOGI INDONESIA, 2012)
Quality of Meat and Its Other Body Parts of Sunda Pangolin (Manis javanica Desmarest, 1822). Sunda pangolin (Manis javanica Desmarest, 1982) is a scaly mammal protected and endangered due to illegal hunting and uncontrolled trade. Because this animal?s biological information has not been widely known, it is necessary to study its various aspects. This study aims to determine the quality of meat and its other body parts of sunda pangolin.Research material used are meat and its other body parts of two male pangolins. The observed chemical composition includes water content, ash, protein, fat, energy, amino acids, fatty acids, cholesterol, EPA, and DHA. Physical quality includes pH and cooking loss. The results showed pangolin meat contains 73.99% water, 0.98% ash, 22.87% protein, 1.63% carbohydrate, 1027.70 cal / g gross energy, and cholesterol 18.89 mg/100 g. The concentrations of essential amino acids of pangolin which are high compared to other wildlife are arginine (1.63%), threonine (1.04%), isoleucine (1.03%), and leucine (1.88%). The content of fatty acids of pangolin meat are lauric (0.30%), myristic (1.20%), palmitic (24.90%), stearic (5.76%), oleic (24.25%), linoleic (2.99%), and linolenic (0.31%). Total EPA and DHA are 9.16 mg/100 g and 16.64 mg/100 g,respectively. Pangolin scales contain protein, gross energy, calcium, phosphorus, 14 kinds of amino acids, EPA and DHA higher than those of its meat. Protein content of pangolin?s body parts from the highest to the lowest is scales > tongue > meat > liver. The pH value of pangolin meat is 6.17 and its cooking loss is 35.12%.Keywords : nutritional values, meat, scale, Manis javanica